MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN MELALUI PERMAINAN BOLA BESAR DI TK ISLAM NUSANTARA - Uut Avi Rustiani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
Rough motor skills are the ability of the body to use large muscles, which involves the whole body such as the muscle activity of the hands and feet in locomotor, non locomotor and manipulative action. One of the activities that can be used is through big ball game.Based on the result of pre-research analysis, the percentage of gross motor ability of children is 27%, cycle 1 is 41%, while at the end of cycle 2 the percentage of gross motor ability improvement of children is 97%. This research is shown to be seen from the change of motor ability of roughly very good class in cycle 2. It can be seen that children are already able to develop rough motor movement through various media with balance, flexibility, children able to train the muscles of the hands and feet, the coordination of foot and eyes, and hand and eye coordination. In the process of learning, children now look very enthusiastic. As has been stated in the interpretation of the results of analysis that this research is said to succeed if there is a minimum increase of 75%. So at the end of this 2nd cycle of research is said to be very successful because the percentage of increase obtained to 97%. This exceeds the minimum limit set by researchers and collaborators. Based on these data, it can be concluded that the rough motor skills of children aged 5-6 years in Islamic Nursery Kindergarten by using a large ball game increased and the results of the process of great ball game improvement is very good.